THE KINSHIP OF JAMBI MALAY LANGUAGE AND MINANGKABAU LANGUAGE - Oktariza, Dodi (Universitas PGRI Sumatera Barat, 2022)
The research is aimed at. 1) describe the correspondence of the sounds of the two languages so that several correspondence rules are produced 2) determine the percentage of cognates of the two languages , and determine the grouping of the two languages. The research was conducted in three stages, namely data collection, data analysis, and the description of data analysis results. At the data collection stage, the method used is observational method and the listening method. The main technique in data collection was elicitation technique, followed by advanced technique, namely face-to-face conversation technique, note-taking technique, and recording technique. At the data analysis stage, the approach used is a quantitative and qualitative approach. A quantitative approach is used to calculate the percentage of kinship based on basic vocabulary based on universal basic vocabulary found in both languages. Meanwhile, a qualitative approach was carried out to show and explain the evidence of the kinship of the two languages. The results of this study were 1.There were twelve sets of sound correspondence rules which were dominantly seen in the ultima and penultimate positions. 2) By using lexicostatistic method, it was found that Jambi Malay and Minangkabau have a kinship around sixty seven percent that belong to the family of languageskey words: correspondence,, Lexicostatistics, Jambi Malay and Minangkabau language